Study the absorption of UV light on optical material upon target distance - 383245 Mohd. Hazimin Mohd. Salleh; Noriah Bidin, 1957-; International Conference on Advancement in Science and Technology (2003 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2003)
40